Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Proceedings of the 2018 ACM International Joint Conference and 2018 International Symposium on Pervasive and Ubiquitous Computi 2018
DOI: 10.1145/3267305.3274156
|View full text |Cite
|
Sign up to set email alerts
|

Community Structures, Interactions and Dynamics in London's Bicycle Sharing Network

Abstract: Bikesharing schemes are transportation systems that not only provide an efficient mode of transportation in congested urban areas, but also improve last-mile connectivity with public transportation and local accessibility. Bikesharing schemes around the globe generate detailed trip data sets with spatial and temporal dimensions, which, with proper mining and analysis, reveal valuable information on urban mobility patterns. In this paper, we study the London bicycle sharing dataset to explore community structur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 19 publications
(23 reference statements)
1
18
0
Order By: Relevance
“…The free-floating shared bicycle is a type of new public transportation, and the research on free-floating shared bicycles is limited. Some research on station-based shared bicycles is referred to in this study [7][8][9][10][11]. Some scholars have tried to analyze the usage of shared bicycles from the perspective of a time series [9,10,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The free-floating shared bicycle is a type of new public transportation, and the research on free-floating shared bicycles is limited. Some research on station-based shared bicycles is referred to in this study [7][8][9][10][11]. Some scholars have tried to analyze the usage of shared bicycles from the perspective of a time series [9,10,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…characteristics of shared bicycles, some studies have identified different purposes of cyclists, such as commuting and recreational usage [7,11,15]. Some studies have proposed the spatial-temporal clustering of bicycles to explore the collective behavior of bike sharing users [8,16,17]. It has been demonstrated that the analyses of the characteristics of shared bicycle trips are helpful for making decisions on the allocation and dispatching of shared bicycles [18][19][20].However, shared bicycles, as an alternative mode of public transportation [21], are embedded in the space where the original public transportation is located.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Fernando Munoz-Mendez et al, 2018 used 1,459,945 ordered O-D pairs from the London station-based BSS from June to July in 2014 and showed that bike usage reflected rush hours. Compared to daytime trajectories, night trajectories were irregular and significantly decreased in number [20]. Employing O-D data pairs from station-based BSS during several months in 2013 and 2014 in Chicago, Zhou et al, 2015 identified and verified clusters where shared bikes are densely used [21].…”
Section: Literature Reviewmentioning
confidence: 99%